The influence of the cultural climate of the training environment on physicians' self-perception of competence and preparedness for practice - Busari, Jamiu O (BioMed Central, 2008)
BACKGROUND: In current supervisory practice, the learning environment in which the training of specialist registrars (SpRs) takes place is important. Examples of such learning environments are the hospital settings and/or geographical locations where training occurs. Our objective was to investigate whether the cultural climate of different learning environments influences physicians' perceived level of competence and preparedness for practice. METHODS: An electronic questionnaire was sent to an equal group of paediatricians who had trained in clinical settings located in Europe and the Caribbean. 30 items (Likert scale 1–4 = totally disagree-totally agree) were used to measure the level of preparedness of the respondents in 7 physician competencies. RESULTS: 42 participants were included for analysis. The distribution of participants in both groups was comparable. The overall perception of preparedness in the Caribbean group was 2.93 (SD = 0.47) and 2.86 (SD = 0.72) in the European group. The European group felt less prepared in the competency as manager 1.81 (SD = 1.06) compared to their Caribbean counterparts 2.72 (SD = 0.66). The difference was significant (p = 0.006). CONCLUSION: The training in the different environments was perceived as adequate and comparable in effect. The learning environment's cultural climate appeared to influence the physician's perception of their competencies and preparedness for clinical practice.